The issue of the ontological status of technology in the concepts of O. Spengler and G. Simondon - Verashchaka, Aliaksei I. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
This article covers the attempt to justify the ontological state of technology from the perspective of the evolution of life. Two strategies are considered here. They are complementing each other; they originate from the same ontology but lead to different conclusions. The analysis is made of the prerequisites for the origin of the technical phenomenon. I am also consider the genesis of technophobiaca approach in the philosophy of technology and attemption of it overcoming within the framework of co-evolution of man and machine.
Keywords: philosophy of technology; ontology of technology; Gestell; demonic technology; technophobia; philosophy of life; life form